A review of induction and attachment times of wetting thin films between air bubbles and particles and its relevance in the separation of particles by flotation - Albijanic, Boris; Ozdemir, O.; Nguyen, A.; Bradshaw, D. (Elsevier BV, 2010)
Bubble-particle attachment in water is critical to the separation of particles by flotation which is widely used in the recovery of valuable minerals, the deinking of wastepaper, the water treatment and the oil recovery from tar sands. It involves the thinning and rupture of wetting thin films, and the expansion and relaxation of the gas-liquid-solid contact lines. The time scale of the first two processes is referred to as the induction time, whereas the time scale of the attachment involving all the processes is called the attachment time. This paper reviews the experimental studies into the induction and attachment times between minerals and air bubbles, and between oil droplets and air bubbles. It also focuses on the experimental investigations and mathematical modelling of elementary processes of the wetting film thinning and rupture, and the three-phase contact line expansion relevant to flotation. It was confirmed that the time parameters, obtained by various authors, are sensitive enough to show changes in both flotation surface chemistry and physical properties of solid surfaces of pure minerals. These findings should be extended to other systems. It is proposed that measurements of the bubble-particle attachment can be used to interpret changes in flotation behaviour or, in conjunction with other factors, such as particle size and gas dispersion, to predict flotation performance. © 2010 Elsevier B.V. All rights reserved.